2017
DOI: 10.21833/ijaas.2017.012.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating economic growth-energy consumption-environmental degradation nexus in China

Abstract: The impact of energy consumption and its relationship with macroeconomic variables is always the concern of policy authorities. In this paper, we conduct empirical analyses on testing the inter-relationship between energy consumption with economic growth (GDP) and environmental degradation (greenhouse gases emissions). Our main objective is to indicate the direction of causal (uni-directional or bi-directional) relationship on these variables and the dynamic of the relationship (symmetric or asymmetric and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Saidi and Hammami (2015) analysed the relation between CO 2 emissions, economic growth, and energy consumption in 58 countries and observed that the three indicators are complementary. Sek and Chu (2017) investigated the dynamic relation between the three variables in a country with a high energetic consumption that is China. They noticed a bi-directional relation between energy consumption and greenhouse gases emissions and a uni-directional relation between economic growth and short time energy consumption in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saidi and Hammami (2015) analysed the relation between CO 2 emissions, economic growth, and energy consumption in 58 countries and observed that the three indicators are complementary. Sek and Chu (2017) investigated the dynamic relation between the three variables in a country with a high energetic consumption that is China. They noticed a bi-directional relation between energy consumption and greenhouse gases emissions and a uni-directional relation between economic growth and short time energy consumption in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, mainly the causality relations among greenhouse gas emissions, energy consumption and economic growth have been investigated [25,26]. Also, the relations between real GDP per capita, urbanization rate, ratio of tertiary to secondary industry, ratio of renewable energy, and fixed assets investment have been analyzed [27].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Researchers have studied the associations between economic growth, energy consumption and environmental change for decades [4,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Some researchers focused on exploring the relationships between economic growth, energy use such as electricity consumption and greenhouse gases (GHG) emissions in a single country or city [31,32,35,36,40,[42][43][44] while others preferred the study of the relationships using panel data i.e., multiple countries simultaneously [34,[37][38][39]41,[45][46][47][48]. Specifically, Bilan et al [46] reported that there is a long-run causal relationship running from the use of renewable energy in the form of capital and human resources to economic growth in the form of GDP per capita in EU member countries.…”
Section: Economic Growth and Environmental Changementioning
confidence: 99%